Particle bombardment technology for gene transfer - Yang, Ning-Sun; Christou, Paul (Oxford University Press, 1994)
Examining the full range and versatility of particle bombardment technology, the contributors to this volume describe the essential protocols, as well as successful applications such as crop improvement and human gene therapy. Hardware design, recombinant DNA and tissue culture techniques, and other technical issues are included. The book brings together recent developments and advancements in the field and unifies plant, microorganism and mammalian systems in a concise volume that enables the reader to access all important theoretical, mechanical and historical aspects of the technology.